Synthesis and Characterization Of Silver Nanoparticles Using Water Extract of Sarang Semut (Myrmecodia pendans) For Blood Glucose Sensors - Rosalinda Zeniona Maarebia; Abdul Wahid Wahab; Paulina Taba (Hasanuddin University, 2019)
The principles of green chemistry in nanotechnology is one of the key issues in nanoscience research. Biosynthesis of nanoparticles using plant extract is an eco- friendly approach which eliminates the need for using physical and chemical techniques. A green synthetic route for the production of stable silver nanoparticles (AgNPs) by using aqueous silver nitrate as metal precursor and Myrmecodia pendans extract as bioreductor and PVA as stabilizer is being reported for the first time. In this case, the synthesis of silver nanoparticles (AgNPs) was carried out by reduction method. The bio-reduction and stabilization of so formed silver nanoparticles was monitored by UV-Vis spectrophotometry. Maximum absorption of AgNPs using Polyvinyl Alcohol (PVA) was at wavelength 408.50 nm, whereas that of AgNPs without using PVA was at wavelength of 408 nm. SEM images showed that the morphology of AgNPs was globular. An average size of silver nanoparticles using PVA and without using PVA was 78.3 and 76.1 nm, respectively. The results of X-Ray Diffraction (XRD) displayed the same peak pattern with that of the standard silver metal showing that the resultant particles are silver nanoparticles having FCC structure. Analysis of glucose levels in blood using silver nanoparticles based sensors showed glucose concentration of 71.71 mg / dL.